Description of Member Disciplines in Scouting Extracurricular Activities at Vocational High School (SMKN) 1 Sintuk Toboh Gadang Padang Pariaman Regency - Laila, Ela; ‘Aini, Wirdatul (Indonesian Journal of Contemporary Education, 2019)
This study is motivated by the success of scouting activities at Vocational High School (SMKN) 1 Sintuk Toboh Gadang Padang Pariaman Regency. Evident from the high interest of students participating in scout extracurricular activities compared to other extracurricular activities, scouting members participated, seriously participated in the activities, outstanding members participated in various competitions within the Province and outside the province. The researcher suspects the cause of the success of the activity due to the discipline of scout members. This type of study is descriptive quantitative. The population in the study were 82 scout members. The sampling technique uses Stratified Random Sampling. Samples were taken in each class as much as 60%, namely 49 members. The technique of collecting data uses a questionnaire. The data collection tool uses a questionnaire. The data analysis technique uses the percentage formula. The results of the study show the discipline of scout members from aspects (1) mental attitude, (2) implementation of rules, (3) behavior, categorized very well. It was proven that most students stated "often" from the statement given